Determinants of environmental rehabilitation expenditure among manufacturing firms in Shaggar city administration, Ethiopia - Urgessa Tilahun Bekabil; M.K. Jayamohan; Amsalu Bedemo Beyene (Sustainable Futures)
Industrial growth is essential for economic development, but it can threaten the environment if not properly managed. This study investigates the determinants of environmental rehabilitation expenditures by industrial firms. Researchers deliberately chose Shaggar city as their study area since Shaggar is located in the surrounding areas of Addis Ababa and hosts many manufacturing firms. This study used simple random sampling to include 303 manufacturing firms to determine these parameters. Owing to the nature of the dependent variable, which is a censored form of expenditure, researchers have employed the censored Tobit model in their quantitative data analysis. The results of both the censored Tobit and Tobit multiplicative heteroscedasticity models revealed that the following factors influence manufacturing firms' expenditures on environmental rehabilitation: firm age, foreign capital involvement during initial investment, access to technology, solid waste disposal facilities, initial capital, energy cost, government incentives, R&D cost, and wastewater treatment. The finding implies that firms that engage heavily in R&D tend to develop environmentally friendly technologies and those that experience increased costs in energy consumption are likely to enhance their environmental strategies, including rehabilitation efforts. The findings of this study draw the attention of stakeholders, researchers, and policymakers to the need to ensure that manufacturing firms operate in an environmentally friendly manner and to further investigate the relative impacts of foreign and domestic capital investment on environmental rehabilitation costs.